“Somos todos macacos”: a trajetória textual e a entextualização do slogan em blogs e jornais online - Vilela, Érika Pereira (2016)
This research aims at analyzing the textual history of the slogan "Somos Todos Macacos" in articles published in blogs and online newspapers; it also intends to investigate the entextualization processes mobilized in opinion articles during slogan trajectory, the first one entitled "The class of Daniel Alves and Neymar to combat racism. Or: I am also monkey", published on the magazine's website Veja and the second: "No, we are not monkeys. We are human!", released Afropress portal. The work are speech performative acts Austin ([1962] 1990) and Derrida ([1972] 1988), the concept of race proposed by Queer Theory (SOMMERVILLE, 2000; SULLIVAN, 2003; BUTLER, [1990] 2003; BARNARD, 2004; LOURO, 2004 WILCHINS, 2004). This is an ethnographic research (HINE, 2000), the analysis material is composed by the slogan "We Are All Monkeys" and two articles about it on blogs and online newspapers. The data analysis are based on theoretical-analytical constructs textual trajectory Blommaert (2006, 2010), entextualization processes (BAUMAN; BRIGGS, 2006) and indexical clues indicated by Wortham (2001). During the history, the slogan traveled of social networking to online media, with 51 texts found through Google search. The analysis indicates that even with different racial discourses of Brazilian society, those who make reference to equality and racial democracy still permeate most of the buildings on race. In the article published on the magazine's website See, we see support for the silencing of racial reflection, while the analysis of the text published by Afropress, by contrast, suggests the importance of the complaint, the punishment and the discussions on the subject.